2013
DOI: 10.1016/j.jiph.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of varicella-zoster virus in the prevaccine era: A population-based study in Izmir, Turkey

Abstract: A large proportion of the participants were found to be immune to VZV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
3
13
0
1
Order By: Relevance
“…In Pakistan, a tropical pattern of VZV epidemiology was found with a seroprevalence of 42.5% in the 11-15- year age group and 46.7% in the 16-20- year age group [ 27 ]. Our findings are consistent with two studies in Turkey; in one of them18.8% of adolescents and 11.7% of young adults were seronegative for VZV [ 28 ], and in the other one, 94.3% of individuals older than 15 were seropositive for VZV [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…In Pakistan, a tropical pattern of VZV epidemiology was found with a seroprevalence of 42.5% in the 11-15- year age group and 46.7% in the 16-20- year age group [ 27 ]. Our findings are consistent with two studies in Turkey; in one of them18.8% of adolescents and 11.7% of young adults were seronegative for VZV [ 28 ], and in the other one, 94.3% of individuals older than 15 were seropositive for VZV [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported that living in urban areas, living in a large family (≥ 4 people) and children with more siblings are factors associated with higher varicella seroprevalence. Many studies have found no gender difference for varicella seroprevalence (2,3,16,17,(28)(29)(30). Consistent with the current study, varicella seroprevalence was not associated with household size, income, occupation and education in a population-based study in Izmir in 2009-2010 (16).…”
Section: Discussionsupporting
confidence: 88%
“…[ 86 ] Another study in Izmir has investigated varicella seroprevalence among 2136 healthy aged 15 years and above. [ 87 ] It has shown that VZV seropositivity was high (94.3%), and there was significant difference between VZV seroprevalence in urban and rural. Furthermore, a large proportion of the population in Izmir was naturally immunized against varicella.…”
Section: Turkeymentioning
confidence: 99%
“…Furthermore, a large proportion of the population in Izmir was naturally immunized against varicella. [ 87 ]…”
Section: Turkeymentioning
confidence: 99%